Nicotine Chewing Gum and Its Correlation with Smoking Cessation: A Meta-Analysis - Roni Hartono; Lina Eta Safitri (Masters Program in Public Health, 2021)
Background: Smoking is a human behavior that has a very bad impact on health. Mortality and morbidity due to smoking cannot be under